2016
DOI: 10.1177/1350507616651387
|View full text |Cite
|
Sign up to set email alerts
|

Creative leadership as a collective achievement: An Australian case

Abstract: Abstract:In this paper we examine the construct of 'leadership' through an analysis of the social practices that underpinned the Australian Broadcasting Corporation (ABC) television production entitled The Code. Positioning the production within the neo-bureaucratic organisational form currently adopted by the global television industry, we explore new conceptualisations of the leadership phenomenon emerging within this industry in response to the increasingly complex, uncertain, and interdependent nature of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…Still, we find that the leadership-as-practice approach goes further, as it explores leadership as an emergent phenomenon in the complex and dynamic processes of the creation of relationships between leaders and employees in particular contexts and practices (Day et al 2014;Uhl-Bien and Ospina 2012;Gardner et al 2010;Avolio et al 2009;DeRue and Ashford 2010). Leadership needs to be acknowledged as a collective achievement (Crevani and Endrissat 2016;Dovey et al 2016). Here, practice is characterised by common language, communication and physical expression; it is where leaders and followers together make sense of situations and construct ways of relating and acting (Cunliffe 2001;Shotter and Cunliffe 2003).…”
Section: Leadership As Practicementioning
confidence: 95%
See 3 more Smart Citations
“…Still, we find that the leadership-as-practice approach goes further, as it explores leadership as an emergent phenomenon in the complex and dynamic processes of the creation of relationships between leaders and employees in particular contexts and practices (Day et al 2014;Uhl-Bien and Ospina 2012;Gardner et al 2010;Avolio et al 2009;DeRue and Ashford 2010). Leadership needs to be acknowledged as a collective achievement (Crevani and Endrissat 2016;Dovey et al 2016). Here, practice is characterised by common language, communication and physical expression; it is where leaders and followers together make sense of situations and construct ways of relating and acting (Cunliffe 2001;Shotter and Cunliffe 2003).…”
Section: Leadership As Practicementioning
confidence: 95%
“…The leadership-as-practice approach to leadership studies represents an alternative to the mainstream leadership literature that informs leaders on what they ought to do in order to lead effectively (Arnulf and Larsen 2015). In a practice-based approach, the focus is on the daily practice of leadership and how actors 'get on' with the work of leadership as well as the emergent and dynamic processes of these practices (Whittington 1996;Chia and Holt 2006;Crevani and Endrissat 2016;Dovey et al 2016).…”
Section: Leadership As Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Leadership in this context is often not fixed but fleeting, not extraordinary but mundane. Yet, it may require the enactment of recurrent interpersonal practices such as fierce advocating along with practical reflexivity, valuing of dissent, commitment to learning, and willingness to extend trust (Dovey et al, 2017). Smith et al (2017) found in their study of an interorganizational research consortium that leadership revolved around the creation and enactment of a shared social identity.…”
Section: Identitymentioning
confidence: 99%